PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA TRANSPORTASI UMUM TRANSJAKARTA SELAMA MASA PANDEMI COVID-19 - Ika Puji Saputri; Vely Randyantini; Bagus Nurcahyo (GoAcademica Research dan Publishing, 2022)
This study aims to analyze the effect of service quality and the value of each service quality indicator on the satisfaction of Transjakarta public transportation users during the Covid-19 pandemic. This study uses multiple linear regression analysis. The population in this study are users of Transjakarta transportation services in the Jabodetabek area whose numbers are not known with certainty. The sample in the study was 100 respondents. The sampling technique in this study used purposive sampling. The results showed that the quality of service had a positive and significant effect on the satisfaction of Transjakarta users during the COVID-19 pandemic. In addition, the value of each service indicator also has a positive and significant impact on the satisfaction of Transjakarta users during the COVID-19 pandemic.